Glycogen synthase kinase‐3 inhibition overcomes epithelial‐mesenchymal transition‐associated resistance to osimertinib in EGFR‐mutant lung cancer. Issue 7 (11th June 2020) - Fukuda, Koji; Takeuchi, Shinji; Arai, Sachiko; Kita, Kenji; Tanimoto, Azusa; Nishiyama, Akihiro; Yano, Seiji
Abstract: A novel epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitor, osimertinib, has marked efficacy in patients with EGFR ‐mutant lung cancer. While epithelial‐mesenchymal transition (EMT) plays a role in the resistance to various targeted drugs, its involvement in EGFR‐inhibitor resistance remains largely unknown. Preclinical experiments with osimertinib‐resistant lung cancer cells showed that EMT was associated with decreased microRNA‐200c and increased ZEB1 expression. In several resistant clone cells, pretreatment with the histone deacetylase inhibitor quisinostat helped overcome the resistance by reverting EMT. Furthermore, drug screening from a library of 100 kinase inhibitors indicated that Glycogen synthase kinase‐3 (GSK‐3) inhibitors, such as LY2090314, markedly inhibited the growth and induced apoptosis of resistant cells, specifically those with a mesenchymal phenotype. These results suggest that GSK‐3 inhibition could be useful to circumvent EMT‐associated resistance to osimertinib in EGFR ‐mutant lung cancer. Abstract : Summary scheme of the role of microRNA (miR)‐200c in the activation of the glycogen synthase kinase (GSK)‐3/AKT axis in osimertinib‐sensitive and osimertinib‐resistant cells. EMT, epithelial‐mesenchymal transition.